What babies need: accelerating access to current and novel antiretroviral drugs in neonates through pharmacokinetic studies. Issue 9 (September 2022) - Jacobs, Tom G; Schouwenburg, Stef; Penazzato, Martina; Archary, Moherndran; Ruel, Theodore D; van den Anker, John; Burger, David M; Cressey, Tim R; Abrams, Elaine J; Lyall, Hermione; Bekker, Adrie; Colbers, Angela; et al.
Summary: Although 23 antiretroviral drugs are approved for use in adults, only six are approved by regulatory authorities for use in term neonates born to women with HIV, with even fewer options for preterm neonates. A major hurdle for approvals is the delay in the generation of pharmacokinetic and safety data for antiretrovirals in neonates. The median time between the year of approval from the US Food and Drug Administration of an antiretroviral agent for adults and the first publication date for pharmacokinetic data in neonates less than 4 weeks old is 8 years (range 2–23 years). In this Viewpoint, we address pharmacokinetic research gaps and priorities for current and novel antiretroviral use in neonates. We also consider the challenges and provide guidance on neonatal clinical pharmacology research on antiretroviral agents with the goal of stimulating research and expediting the availability of safe medications for the prevention and treatment of HIV in this vulnerable population.